Kemandirian dan Minat Berwirausaha pada Mahasiswa Aktif Angkatan 2020 - Nanda, Nabela Febika Areta; Pratitis, Niken Titi; Arifiana, Isrida Yul (Jurnal Psikologi Perseptual, 2024)
The decreasing number of jobs and the increasing number of students who are more oriented towards finding work have the potential to increase unemployment rates in the future. Students as people who will enter the world of work need an interest in entrepreneurship as a basis for opening new jobs. This study aims to see whether student independence is related to their interest in entrepreneurship. The design of this study is quantitative correlational with the Spearman's Rho analysis method. A total of 247 students were involved in this study, collected using quota sampling techniques taken from 2686 students of the 2020 intake of the Universitas 17 Agustus 1945 Surabaya with the calculation of the Isaac and Michael table. The measuring instruments used were the independence scale (α:0.932) and the entrepreneurial interest scale (α:0.944). The results of the study showed a positive correlation between the level of independence and students' entrepreneurial interest (r:0.993; p 0.001). A high level of independence makes students believe in their own abilities and not depend on external factors so that they can overcome thoughts about the risk of failure so that students become more interested in becoming entrepreneurs.Semakin berkurangnya lapangan pekerjaan serta semakin banyaknya mahasiswa yang lebih berorientasi mencari kerja menjadi potensi semakin tingginya angka pengangguran di masa mendatang. Mahasiswa sebagai insan yang akan terjun pada dunia kerja memerlukan minat untuk berwirausaha sebagai dasar membuka lapangan pekerjaan yang baru. Tujuan dari penelitian adalah untuk melihat ada tidaknya korelasi antara tingkat kemandirian dengan minat berwirausaha mahasiswa. Desain penelitian ini adalah kuantitatif korelasional dengan metode analisa Spearman’s Rho. Sebanyak 247 mahasiswa terlibat dalam penelitian ini yang dihimpun menggunakan teknik quota sampling yang diambil dari 2686 mahasiswa angkatan 2020 Universitas 17 Agustus 1945 Surabaya dengan perhitungan tabel Isaac dan Michael. Alat ukur yang digunakan adalah skala kemandirian (α:0,932) dan skala minat berwirausaha (α:0,944). Hasil penelitian menunjukkan adanya korelasi positif antara tingkat kemandirian dengan minat berwirausaha mahasiswa (r=0,993; p0,001). Tingkat kemandirian yang tinggi menjadikan mahasiswa meyakini kemampuan dirinya dan tidak tergantung pada faktor eksternal sehingga dapat mengatasi pemikiran akan resiko kegagalan sehingga mahasiswa menjadi lebih berminat untuk berwirausaha.